Efficient production of the β-ionone aroma compound from organic waste hydrolysates using an engineered Yarrowia lipolytica strain - Chen, Shuyi; Lu, Yanping; Wang, Wen; Hu, Yunzi; Wang, Jufang; Tang, Shixing; Lin, Carol Sze Ki; Yang, Xiaofeng (Frontiers in Microbiology, 2022)
This study demonstrates the feasibility of establishing a natural compound supply chain in a biorefinery. The process starts with the biological or chemical hydrolysis of food and agricultural waste into simple and fermentative sugars, followed by their fermentation into more complex molecules. The yeast strain, Yarrowia lipolytica, was modified by introducing high membrane affinity variants of the carotenoid cleavage dioxygenase enzyme, PhCCD1, to increase the production of the aroma compound, β-ionone. The initial hydrolysis process converted food waste or sugarcane bagasse into nutrient-rich hydrolysates containing 78.4 g/L glucose and 8.3 g/L fructose, or 34.7 g/L glucose and 20.1 g/L xylose, respectively. During the next step, engineered Y. lipolytica strains were used to produce β-ionone from these feedstocks. The yeast strain YLBI3120, carrying a modified PhCCD1 gene was able to produce 4 g/L of β-ionone with a productivity of 13.9 mg/L/h from food waste hydrolysate. This is the highest yield reported for the fermentation of this compound to date. The integrated process described in this study could be scaled up to achieve economical large-scale conversion of inedible food and agricultural waste into valuable aroma compounds for a wide range of potential applications.